Overshooting and Dollarization in the Democratic Republic of the Congo - Beaugrand, Philippe (IMF Working Papers; Working Paper ;, 2003)
The paper develops an interpretation of volatile exchange rate movements in a dollarized economy with very high rates of inflation. Differences between the rate of inflation and currency depreciation (over- or undershooting of the exchange rate) are seen as a proxy for changes in the relative demand for domestic and foreign currency. A simple model is calibrated for the Democratic Republic of the Congo in the 1990s and is used to derive estimates of the rate of dollarization.